Prevailing Leadership Styles by School Principals in Jordan According to Goleman’s Model of Leadership - Bani Hani , Mohammad; Mustafa, Amera (Jordan Journal of Educational Sciences, 2016)
The purpose of this study was to identify the dominant leadership style adopted by school principals in Qasabet Irbid, based on Goleman’s model of leadership, and as perceived by teachers. The study employed a random sample of (216) teachers of public and private schools in Irbid. A questionnaire of (34) items, representing the (6) leadership styles of Golman was constructed. These styles were: visionary, coaching, affiliative, democratic, pace-setting, and coercive. The study revealed that the visionary style appeared to be common the most, followed by the affiliative, the coaching and the democratic, the pacesetting, and the coercive were the least common. The study found significant differenceces attributed to the experience’s variable in favor of teachers with least experience. Also, there were differences on schools’ variable favoring the private ones. There were no significant differences with respect to gender and level of education. In light of results, recommendations were made by researchers